2012
DOI: 10.1111/j.1445-5994.2010.02402.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of empirical continuous positive airway pressure (CPAP) treatment versus initial portable sleep monitoring followed by CPAP treatment for patients with suspected obstructive sleep apnoea

Abstract: An ambulatory approach with portable sleep monitoring for diagnosing OSA before a CPAP trial can identify more patients who would adhere to CPAP at 6 months than empirical CPAP treatment alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…None of the studies found significant differences in disease management parameters. [77][78][79]92,93,99,102,103 In most of the studies, patients underwent both level 1 and level 3 tests to avoid the risk of internal bias due to differences between study groups. In all of the simultaneous studies, level 3 tests were scored manually by the same technician who scored the level 1 test, which may have resulted in observer bias.…”
Section: Diagnostic Accuracy Of Sleep Testsmentioning
confidence: 99%
“…None of the studies found significant differences in disease management parameters. [77][78][79]92,93,99,102,103 In most of the studies, patients underwent both level 1 and level 3 tests to avoid the risk of internal bias due to differences between study groups. In all of the simultaneous studies, level 3 tests were scored manually by the same technician who scored the level 1 test, which may have resulted in observer bias.…”
Section: Diagnostic Accuracy Of Sleep Testsmentioning
confidence: 99%